Analogical Reasoning in Geometry Proofs - Anass Bayag; Michael J. Bosse; John Sevier (University of Maribor Press, 2021)
This study aimed at investigating six high school students' use of analogies while working through geometry proofs in group settings. Along with the analogies used by students and analysis of how they were used, as well as discourse analysis, we investigate students' meta-proof comments to glean some interpretation of students' beliefs about proofs. Overall, this study found that students had different beliefs about the nature and process of proofs and used and understood analogical reasoning in idiosyncratic ways. However, it was also found that students' greater use of analogies did not automatically lead to more success with proofs.